Separation of the N/CH Mixture through Hydrate Formation in Ordered Mesoporous Carbon - Qiaobei Dong; Wei Su; Xiuwu Liu; Jia Liu; Yan Sun (Adsorption Science & Technology)
A method to separate a gaseous mixture of nitrogen and methane by exploiting the difference between hydrate-formation pressures of nitrogen and methane has been developed to enrich the concentration of methane in low-quality coal-bed methane. The equilibrium isotherms of pure N 2 and CH 4 in CMK-3, a mesoporous carbon material, in the presence of water are measured to determine the optimal separation parameters. Tetrahydrofuran (THF) was added to the water to lower the pressures at which the gas hydrates are formed. A gaseous mixture containing 50% methane was fed through a bed filled with CMK-3 in which a THF solution of 5 mmol/g was pre-adsorbed. The final methane concentration was higher than 70% at 275.15 K.